EXPERIENCE OF BODILY PAIN IN THE WORKPLACE AS A SPECIFIC FACTOR FOR THE PROFESSIONAL BURNOUT OF A DOCTOR - Мария Викторовна Яшникова; Лилия Темурхановна Федорова; Елена Леонидовна Потеряева; Елена Леонидовна Смирнова (Medicina v Kuzbasse, 2024)
Professional burnout is a complex interdisciplinary problem at the junction of hygiene, psychology, psychophysiology and physiology, which implies the possibility of the influence of physiological abnormalities on habitual psycho-emotional reactions during the work process.